1999
DOI: 10.1007/978-3-540-49460-7_62
|View full text |Cite
|
Sign up to set email alerts
|

Luminosity Function of Cluster Galaxies

Abstract: Abstract. We initiated a large project aimed to estimate the Luminosity Function of galaxies in clusters and to evaluate its relation to cluster morphology. With this paper we deem necessary to outline the general procedures of the data reduction and details of the data analysis. The cluster sample includes the brightest southern ROSAT all-sky survey clusters with z < 0.1. These have been observed in three colours g, r, i, and mapped up to a few core radii using a mosaic of CCD frames. E/S0 galaxies in the clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…The choice is the most reasonable one following the work by Sandage et al (1985) on the Virgo cluster; it is evident from the data of the present analysis, Figs. 1 and 2 and as indicated also in Molinari et al (1998) and references therein. In a cluster, as it is very evident also from our data, the bright galaxies are located in the central region and these are the galaxies that are fitted by the Gaussian component of the LF.…”
Section: The Standard Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…The choice is the most reasonable one following the work by Sandage et al (1985) on the Virgo cluster; it is evident from the data of the present analysis, Figs. 1 and 2 and as indicated also in Molinari et al (1998) and references therein. In a cluster, as it is very evident also from our data, the bright galaxies are located in the central region and these are the galaxies that are fitted by the Gaussian component of the LF.…”
Section: The Standard Analysissupporting
confidence: 63%
“…The detailed description of the observations, the data analysis and the algorithms we used can be found in the papers by Molinari et al (1998), Moretti et al (1999), and the laurea thesis by Moretti (1997), Ratti (1998), andParolin (2002). As we want to present the results from the analysis of 7 clusters of the original sample, we give here just few informations to ease the reading (see Table 1).…”
Section: The Luminosity Functionmentioning
confidence: 99%
“…Evidence of a steep LF of field galaxies at infrared wavelength come from Szokoly et al (1998) who find a slope α = −1.3 and from Bershady et al (1999) who estimate α = −1.6. Other evidence in favor of α −1 come from the results obtained on optically selected samples of field galaxies (Marzke et al 1994(Marzke et al , 1997Zucca et al 1997) and of cluster galaxies (De Propris et al 1998;Lobo et al 1997;Bernstein et al 1995;Molinari et al 1998). However, such a steep LF, which contributes substantially to the galaxy counts at optical wavelengths (see e.g.…”
Section: Comparison With Modelsmentioning
confidence: 97%
“…The CFH12K camera is made of 12 2K×4K CCDs (hereafter, we will label the various CCDs from A to L anticlockwise from the south east corner). A global sketch of our field, together with those previously observed by Molinari et al (1998) and by our team are shown in Fig. 1, superimposed on the positions of the galaxies with redshifts belonging to the cluster (see the Durret et al (1999b) catalogue).…”
Section: Observations Reduction and Detectionsmentioning
confidence: 99%
“…Positions of all the galaxies (relatively to the cD) with redshifts in Abell 496 from the Durret et al (1999b) catalogue (crosses). The large rectangle shows the size of the present image; the small squares forming a sort of cross in the center correspond to the CCD catalogue by Slezak et al (1999); the squares drawn with dotted lines indicate the fields covered by Molinari et al (1998).…”
Section: Observations Reduction and Detectionsmentioning
confidence: 99%